Assessment of Culturable Tea Rhizobacteria Isolated from Tea Estates of Assam, India for Growth Promotion in Commercial Tea Cultivars - Dutta, Jintu; Handique, Pratap J.; Thakur, Debajit (Frontiers in Microbiology, 2015)
In the present study, 217 rhizobacterial isolates were obtained from six different tea estates of Assam, India and subjected to preliminary in vitro plant growth promotion (PGP) screening for indole acetic acid (IAA) production, phosphate solubilization, siderophore production and ammonia production. 50 isolates showed all the PGP traits and 5 isolates did not exhibit any PGP traits. These 50 potential isolates were further analyzed for quantitative estimation of the PGP traits along with the aminocyclopropane-1-carboxylate (ACC) deaminase, protease and cellulose production. After several rounds of screening, four rhizobacteria were selected based on their maximum ability to produce in vitro PGP traits and their partial 16S rRNA gene sequence analysis revealed that they belong to Enterobacter lignolyticus strain TG1, Burkholderia sp. stain TT6, Bacillus pseudomycoides strain SN29 and Psedumonas aeruginosa strain KH45. To evaluate the efficacy of these four rhizobacteria as plant growth promoters, three different commercially important tea clones TV1, TV19 and TV20 plants were inoculated with these rhizobacteria in greenhouse condition and compared to the uninoculated control plants. Though, all the rhizobacterial treatments showed an increase in plant growth compared to control but the multivariate PCA analysis confirmed more growth promotion by TG1 and SN29 strains than the other treatments in all three clones. To validate this result, the fold change analysis was performed and it revealed that the tea clone TV19 plants inoculated with the E. lignolyticus strain TG1 showed maximum root biomass production with an increase in 4.3 fold, shoot biomass with increase in 3.1 fold, root length by 2.2 fold and shoot length by 1.6 fold. Moreover, two way ANOVA analysis also revealed that rhizobacterial treatment in different tea clones showed the significant increase (p<0.05) in growth promotion compared to the control. Thus, this study indicates that the potential of these indigenous PGPR isolates to use as microbial inoculation or biofertilizer for growth promotion of tea crops.